Innovations for Agricultural Development in Egypt: Combining digital technologies to inclusive business approaches within agribusiness value chain strategy - Fiani, Dorra (2019)
As part of the IFPRI Egypt Seminar in partnership with the World Bank, IFPRI Egyprt seminar “Innovations for Agricultural Development in Egypt”.